2019
DOI: 10.1111/jpn.13195
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of stress response, growth and development of uteri in post‐weaning gilts challenged with zearalenone and estradiol benzoate

Abstract: The objective of this study was to evaluate the effects of zearalenone (ZEA) and estradiol benzoate (EB) on stress injury and uterine development in post‐weaning gilts. Thirty healthy post‐weaning female gilts (Duroc × Landrace × Large White) aged 28–32 days were randomly allocated to three treatments as follows: (a) basal diet (Control), (b) basal diet plus 1.0 mg/kg purified ZEA (ZEA) and (c) basal diet plus 0.75 ml (1.5 mg) EB per pig at 3‐days intervals by intramuscular injection (EB). The serum estradiol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…Most studies have established that ZEA can induce the expression of Hsp70. For example, compared with the control group, it can be clear that in the uterus of weaning sows, the 1.04 mg/kg ZEA arginine treatment sample has a higher level of Hsp70 mRNA [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have established that ZEA can induce the expression of Hsp70. For example, compared with the control group, it can be clear that in the uterus of weaning sows, the 1.04 mg/kg ZEA arginine treatment sample has a higher level of Hsp70 mRNA [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the mechanism whereby ZEA induces the up-regulated expression of Hsp70, it is speculated that ZEA induces stress via a disruption of serum hormones and an upregulation of growth hormone receptor expression [ 20 ]. In addition, it has been established that apoptosis induced by ZEA (60, 90, and 120 μmoL) is mediated dose dependently via a caspase-3- and caspase-9-dependent mitochondrial pathway [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that ZEA at dietary concentrations ranging from 1.1 to 3.2 mg/kg increased hyperplasia of submucosal smooth muscles in the uteri of gilts [ 8 ], and, at concentrations of 0.5 to 1.5 mg/kg, ZEA increased the uterine organ index and the thickness of the myometrium and endometrium [ 9 , 10 ]. However, the relationship between the uterine cells changes and uterine hypertrophy induced by ZEA has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The most common toxic effect of ZEN is related to reproductive disorders with pigs being the most affected [141]. Pigs are mostly used as the model for research since they possess similar digestive and immune system as humans [142].…”
Section: Mechanism Of Toxicity and Health Effects Of Zearalenonementioning
confidence: 99%